The "Domostroi" : rules for Russian households in the time of Ivan the Terrible - Pouncy, Carolyn (Cornell University Press, 1994)
A detailed and colorful instruction manual on household management in sixteenth-century Russia, the Domostroi gives a fascinating glimpse of the world of the nobility. This "how-to" guide is one of the few sources on the social history and secular life of Russia in the time of Ivan the Terrible. Carolyn Johnston Pouncy here offers, with an informative introduction, the first complete English translation. This melange of admonitions covered the proper Christian life, orders on day-to-day secular life, and practical details on domestic organization. How to arrange hay, visit monasteries, distill vodka, treat servants, entertain clergy, instruct a son or wife, cut out a robe - specific instructions dictated the rules for innumerable aspects of proper behavior. Life was simple for the Domostroi author: "a place for everything and everything in its place." In his universe, Pouncy writes, "pickled mushrooms and clean straw reflected the soul as clearly as acts of charity." It was a world view that prized religious orthodoxy, reliance on tradition, absolute subordination of the individual to family and the state - ideals to which most sixteenth-century Muscovites subscribed without question. Providing a distinct picture, unparalleled elsewhere, of the wealthy, urban household, this book adds an invaluable dimension to our understanding of Russian social and cultural history